Thermophysical properties and solar thermal energy storage performance of phase change composites manufactured by vat photopolymerization 3D printing technique - Er, Yusuf; Guler, Onur; Hekimoglu, Gokhan; Nodehi, Mehrab; Ustaoglu, Abid; Sari, Ahmet; Ozbakkaloglu, Togay (Elsevier, 2023)
Phase change materials (PCMs) refer to a group of semi-solid/liquid materials that have high energy storage capacity that are released during the phase transitioning period. Although the impact of utilizing PCMs are considerable, often suitable conservation from leakage is a major issue for these materials' uses. Considering this issue, this study incorporates a Vat Photopolymerization technique to print a composite resin filament containing lauric acid (LA) used as a PCM. LA were mixed with resin in four different proportions of 20, 30, 40 and 50 vol%, and then printed for testing. To thoroughly analyze the characteristics of the resin/LA composites that were manufactured, a range of tests focusing on mechanical, thermal, and microstructural aspects were carried out on the produced samples. Additionally, solar thermoregulation properties were also investigated using a specifically developed testing instrument. The obtained results show that the highest latent heat enthalpy value (83.7 J/g) was found in 50 % LA added composites that also contained a homogeneous internal structure compared to undoped resin materials. Although 50 % LA additive provides superior heat energy storage, it causes a decrease in mechanical properties, since the resin has five times higher tensile strength than that of LA. Nonetheless, the results show that PCMs (specifically LA, in this case), can be 3D printed in real-time with resins without concerns over the leakage problem. This novel use of PCMs can significantly improve the leaking issue and provide a solid mean for energy storage purposes that can support major insulating and energy savings.
Keywords: Vat photopolymerization; Phase change materials (PCM); Thermal energy storage; Energy efficiency; Additive manufacturing (3D printing)